PENGEMBANGAN PERANGKAT PEMBELAJARAN PENGUASAAN KONSEP IPA SISWA SD KELAS V MELALUI PENDEKATAN SAINTIFIK - Wardani, Rizki Putri (FKIP Universitas Wiraraja, 2019)
The objective of this study was to develop a learning material with scientific approach to practice science attainment concept at grade fifth elementary school. This kind of research was developing research that use 4D model with one group test pretest-postest design. Subject of research was learning material that would be tested in the student of Kebonsari I Tuban elementary school. Data would be analyzed by using qualitative and quantitative. This research consisted of lesson plan, student work sheet, hand book, and science attainment concept test. The result showed that learning material was valid, 3,5 for RPP, 3,4 for LKS, and 3,4 for Booksheet. Learning process was done well by 87,6 %. Student activity by using scientifich approach get well too. The result of science attainment concept showed that clasical studying completeness 80%. Based on the research, it can be concluded that learning material was valid, practical, and effective. So it can be apply in the class.